Abnormal Magnetoresistance Transport Properties of van der Waals Antiferromagnetic FeNbTe2 - Qi, Bao-tao; Guo, Jun-Jie; Miao, Ying-qing; Zhong, Mian-zeng; Li, Bo; Luo, Zi-yan; Wang, Xi-guang; Nie, Yao-zhuang; Xia, Qing-lin; Guo, Guang-hua (Frontiers in Physics, 2022)
The emergence of Two-dimensional (2D) van der Waals magnetic materials have attracted enormous attention due to novel physical phenomena and their potential application in the field of spintronics and information storage technology. Here, we systematic study the magnetic and transport properties of a van der Waals antiferromagnetic material FeNbTe2. The magnetic and magnetoresistance measurement verified its antiferromagnetic properties, spin glass state and negative magnetoresistance effect at lower temperature. In addition, the measurement results of transport also show the existence of angle-dependent anisotropic magnetoresistance in a wide temperature range and anisotropic magnetoresistance inversion in a certain temperature range.